Tissue-specific TCF4 triplet repeat instability revealed by optical genome mapping - Zarouchlioti, Christina; Efthymiou, Stephanie; Facchini, Stefano; Dominik, Natalia; Bhattacharyya, Nihar; Liu, Siyin; Costa, Marcos Abreu; Szabo, Anita; Sadan, Amanda N; Jun, Albert S; Bugiardini, Enrico; Houlden, Henry; et al. (EBioMedicine, 2024)
BACKGROUND: Fuchs endothelial corneal dystrophy (FECD) is the most common repeat-mediated disease in humans. It exclusively affects corneal endothelial cells (CECs), with ≤81% of cases associated with an intronic TCF4 triplet repeat (CTG18.1). Here, we utilise optical genome mapping (OGM) to investigate CTG18.1 tissue-specific instability to gain mechanistic insights. METHODS: We applied OGM to a diverse range of genomic DNAs (gDNAs) from patients with FECD and controls (n = 43); CECs, leukocytes and fibroblasts. A bioinformatics pipeline was developed to robustly interrogate CTG18.1-spanning DNA molecules. All results were compared with conventional polymerase chain reaction-based fragment analysis. FINDINGS: Analysis of bio-samples revealed that expanded CTG18.1 alleles behave dynamically, regardless of cell-type origin. However, clusters of CTG18.1 molecules, encompassing ∼1800-11,900 repeats, were exclusively detected in diseased CECs from expansion-positive cases. Additionally, both progenitor allele size and age were found to influence the level of leukocyte-specific CTG18.1 instability. INTERPRETATION: OGM is a powerful tool for analysing somatic instability of repeat loci and reveals here the extreme levels of CTG18.1 instability occurring within diseased CECs underpinning FECD pathophysiology, opening up new therapeutic avenues for FECD. Furthermore, these findings highlight the broader translational utility of FECD as a model for developing therapeutic strategies for rarer diseases similarly attributed to somatically unstable repeats. FUNDING: UK Research and Innovation, Moorfields Eye Charity, Fight for Sight, Medical Research Council, NIHR BRC at Moorfields Eye Hospital and UCL Institute of Ophthalmology, Grantová Agentura České Republiky, Univerzita Karlova v Praze, the National Brain Appeal's Innovation Fund and Rosetrees Trust.
Keywords: Somatic mosaicism; alely; Humans; lidé středního věku; Triplet repeat expansion-mediated disease; trinukleotidové repetice; Organ Specificity; Female; Aged; Fuchs' Endothelial Dystrophy; Transcription Factor 4; Alleles; transkripční faktor 4; lidé; senioři; Optical genome mapping; Fuchs endothelial corneal dystrophy; nestabilita genomu; Trinucleotide Repeat Expansion; ženské pohlaví; Fuchsova endoteliální dystrofie; Male; Middle Aged; Chromosome Mapping; Trinucleotide repeat expansion disease; Tissue-specific repeat instability; Genomic Instability; mapování chromozomů; expanze trinukleotidových repetic; mužské pohlaví; orgánová specificita; Trinucleotide Repeats